Bienestar subjetivo en personas con Covid persistente - Montenegro S., Monserrat; Milla O., Camila; Martínez S., María Jesús; Mora A., Valentina; Osorio R., Camila; Ramírez-Pereira, Mirliana (Revista Hospital Clínico Universidad de Chile, 2024)
Through this study, we seek to delve into the consequences that Long Covid had in the affective and emotional field of people with this condition, their knowledge about the changes that it entails, and how they perceive their daily lives regarding the repercussions they present. A qualitative, post-positivist, ethnographic research methodology will be used to achieve this. A sociodemographic file was implemented as a data collection technique, and in-depth interviews were conducted. A sociodemographic file was applied as a data collection technique, and in-depth interviews were conducted. According to the inclusion criteria, this study included six people chosen through the snowball technique. In terms of data analysis, interview transcripts were made, coded and categorized concerning the social representations shared by participants. This was followed by a second analysis using the outputs and inputs of Callista Roy’s nursing model. Ultimately, three main categories were obtained: the affective field, where feelings and emotions such as sadness, fear, and concern, among others, stand out; the cognitive field, including the patient’s knowledge about this syndrome, in which it becomes evident the little information available, and the representation field, that describes the significant changes it has meant for them in their daily lives.